Post-traumatic stress disorder in healthcare workers of emergency departments during the pandemic: A cross-sectional study - Bahadırlı, Suphi; Sağaltıcı, Eser (W.B. Saunders, 2021)
Objective: Emergency departments (EDs) were the first application center for Covid-19 patients, as in almost all diseases. For this reason, a serious mental burden has arisen for ED workers. This study was conducted to determine the possible rate of Posttraumatic Stress Disorder (PTSD) and factors that may be associated with PTSD symptom severity in physicians and nurses working in EDs. Methods: This cross-sectional study was conducted with a total of 783 participants, including 406 physicians and 377 nurses working in EDs. The PTSD Checklist for DSM-5; Depression, Anxiety and Stress Scale-21; and a structured questionnaire on sociodemographic and work-related characteristics were administered to the participants. Results: The probable PTSD rate in the total sample was found to be 19.2%. The rate of probable PTSD in physicians (22.9%) was significantly higher than in nurses (15.1%). However, PTSD symptom total scores and PTSD symptom clusters were higher in physicians than in nurses, but there was no difference between the two groups in terms of depression, anxiety and stress levels. High anxiety level, being diagnosed with COVID-19, high depression level, female gender, and having additional chronic disease were predictors of high PTSD symptom severity in physicians. For nurses, high anxiety level, being diagnosed with COVID-19, working with 24-h shifts, high depression level, low work experience (years), low monthly income and having additional chronic disease were the predictors of high PTSD symptom severity. Conclusion: The results of our study showed that both profession groups are at risk for PTSD, and contrary to the existing literature, this rate may be higher in physicians than in nurses. HCWs in the EDs needed protective and supportive mental health models in terms of PTSD.
Keywords: COVID-19; Emergency Departments; Nurses; Physicians; PTSD